PEMIKIRAN ABDULLAH NASHIH ULWAN TENTANG METODE PENDIDIKAN ANAK: TELAAH ATAS BUKU TARBIYAH AL-AULAD FIL ISLAM - Khaerudin, Khamam; Supriyanto, Agus (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2015)
This study will explore on the method of children education in Abdullah Nashih Ulwan?s thought. This research is a library research and used qualitative approach. And in the presentation of the data using descriptive analysis method. Based on the description and analysis of the results of Abdullah Nasikh Ulwan thinking about methods of education of children. Education is a conscious guidance by adults/educators against physical and spiritual development of the students towards the establishment of a major personality.